The Impact of Utilitarian, Hedonic, and Social Value on Purchase Intention through Customer Trust in Live Streaming: A Study of Wardah Beauty Products on TikTok - Adabina Firlyani, Raisa; Millanyani, Heppy (International Journal of Science, Technology & Management, 2025)
This study examines the relationships between utilitarian value, hedonic value, social value, trust in product, trust in platform, and purchase intention in the context of Wardah beauty products on TikTok live streaming. Using Structural Equation Model (SEM) with SmartPLS on 384 respondents, the research found that social value demonstrates the strongest influence on purchase intention (? = 0.368), followed by utilitarian value (? = 0.188) and hedonic value (? = 0.105). Notably, trust in platform significantly influences purchase intention (? = 0.171, p = 0.001), while trust in product does not (p = 0.810). The model explains 62.8% of purchase intention variance with strong predictive relevance (Q² = 0.420). Results indicate that social interactions and platform trust are more crucial than product-specific trust in driving consumer purchase decisions in live streaming commerce. These findings suggest that beauty brands should prioritise social engagement and platform reliability over traditional product-focused marketing strategies.